FORTIFICATION OF OIL FROM CATFISH BELLY FAT (Pangasius hypophthalmus) AND GROUPER FISH MEAT (Epinephelus fuscoguttatus) ON BISCUITS THROUGH CONSUMER ACCEPTANCE - Sri Nova Mardayanti; Mirna Ilza; Syahrul ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe aim of this study was to determine the effect of oil which fortified from catfish belly fat and grouper fish meat to fullfill of formulation according to SNI so prefer by infant. 2 kg of catfish (Pangasiusn hypopthalmus) fat and 2 kg of grouper meat (Epinephelus fuscoguttatus) were extracted. Biscuits fortified with fish oil 0%; 5% and 15% was made from wheat flour, salt, sugar, butter, eggs, cocoa powder and backing soda. Parameters analysis was observed to organoleptic assessment (appearance, odor, texture and flavor (special baby) and proximate analysis (moisture, fat, protein and ash). The result showed that the biscuits was fortified with 5% of fish oil was the best treatment and preferred by consumers with a value 78.75%, water content 4.20%, protein content 8.04%, ash content 1.75% and fat content 10.38%.Keywords: Fortification, Biscuits, Fish oil, Acceptance.